Mineral Content of Clay Soil and Coffee Husk Ash for Soil Stabilization Applications in Geotechnical Engineering - Arissa Sabilla; Rajib Muammar; Ari Juanda (Unversitas Muhammadiyah Mataram, 2025)
This study aims to analyze the mineral composition of clay soil and coffee husk ash, as well as to evaluate the effect of coffee husk ash as a stabilizing agent for clay soil. The main problem addressed is the high plasticity of clay soil, which causes volume changes and reduces bearing capacity, making stabilization methods necessary. The research was conducted by collecting clay soil samples from Kebun Kurma Barbate, Aceh Besar, and coffee husk ash from Aceh Tengah. Mineral composition was analyzed using gravimetric, titrimetric, spectrophotometric, and AAS methods, while soil plasticity was examined through Atterberg limits and specific gravity tests. The results indicate that clay soil contains dominant Silica Oxide (SiO₂) at 42.99% and Aluminum Oxide (Al₂O₃) at 5.63%, contributing to its high plasticity. Meanwhile, coffee husk ash contains 8.30% SiO₂ and 5.22% Calcium Oxide (CaO), which play crucial roles in stabilization. The addition of 5– 25% coffee husk ash reduced the plasticity index from 38.42% to 34.29%, increased soil specific gravity from 2.587 g/cm³ to 2.690 g/cm³, and transformed soil classification from clay to silt. These findings confirm the potential of coffee husk ash as an effective, and sustainable stabilizing material for geotechnical engineering applications